Development of Graphic User Interface (GUI) for the analysis of Outcome Based Education (OBE) - Mohd Hafiz Mohd Sofi (2023)
Currently, most of the systems were conducted by using computers. The main advantage is the processes will become faster rather than manually. Computer programs basically are a gateway with the purpose to be the center point of information when the user could manipulate the data easily. This system is basically providing the ease of evaluating the students using the OBE method. Manually, the lecturers would have to calculate each and every students whether their marks were sufficient to pass the subject or not. Because of these reasons why the author came with the idea to create an OBE GUI System that will be center of evaluation process.